Epistemology of Interpretation of Women's Leadership Verses in the Qur'an ( Comparative Study of Tafsir Al-Ibriz and Tafsir Al-Mishbah ) - Amry, Achmad Amry Zumaro A'laa (Program Studi Ilmu Al-Quran dan Tafsir STIU Darul Quran, 2024)
The epistemology of interpretation critically analyzes the foundation of the theory of knowledge in interpretation. This study examines the sources, methods, and validity of interpretation, focusing on two mufassirs: Bisri Mustofa in Tafsir Al-Ibriz and Quraish Shihab in Tafsir Al-Mishbah. The research method employed is library research, with the interpretation of women's leadership verses as the object, using a descriptive-analytical approach. The author analyzes these verses and epistemological theories as analytical tools. The results reveal the epistemological structure of the two mufassirs: First, the source of interpretation: Bisri Mustofa relies on intellect (ra'yu), while Quraish Shihab uses Qur'anic texts, hadith, opinions of scholars and scientists, reason (ra'yu), and historical data. Second, the methodology of interpretation: both mufassirs use the tahlili (analysis) method; however, Bisri Mustofa adopts a textual approach, whereas Quraish Shihab adopts a more contextual approach. Third, the validity of interpretation: in terms of coherence, both interpretations maintain consistency; in terms of correspondence, Bisri Mustofa's interpretation lacks relevance to the contemporary reality, while Quraish Shihab's interpretation is more aligned with societal realities. Pragmatically, Bisri Mustofa's textual interpretation contributes inadequately to societal issues, whereas Quraish Shihab's contextual approach provides more significant contributions in addressing societal problems.